Resin sealant Monomer Conversion using blue laser-diode or blue LED - Caroline Dudish; Tori Hayes; Frederick Allen Rueggeberg; Rafael Rocha Pacheco (Elsevier, 2024)
OBJECTIVES: Evaluate the degree of monomer conversion (DC) of various resin sealants when photocured using a blue laser-diode or commercially available LED light-curing units (LCUs). METHODS: Three different LCUs were utilized: [LA] blue laser-diode (Monet®, AMD Lasers); [SP] singlepeak blue LED (Elipar™ DeepCure-S, 3M Deutschland GmbH); [MP] multi-peak LED (VALO™ X, Ultradent Products). The spectral irradiance of each LCU was measured using a calibrated integrating sphere/spectral radiometer. Two resin sealants were tested: [CP] Clinpro™ Sealant (3M ESPE) and [XT] UltraSeal XT™ hydro™ (Ultradent Products). Sealants were placed and cured on extracted, human third molars to determine the average sealant clinical thickness: 2.0 mm. Resin sealants (n = 5) were directly dispensed onto the temperature-controlled surface (35oC) of an attenuated total reflectance attachment (Golden Gate; Specac Inc) on a Fourier-transform infrared spectrometer (INVENIO-R, Bruker) inside a custom 3D-printed mold: 2mmh; 5mm-id. LCU distance was standardized at 2.5mm. A Mylar® strip was positioned over the resin sealant for uniform thickness. Exposure durations were defined as: LA-1s, LA-2s, LA-3s, SP-30s, MP-10s (standard mode), and MP-3s ("xtra" mode). The DC (%) was computed using vibrational spectroscopy software (OPUS, Bruker) using peak height ratio changes of aromatic/aliphatic C=C, assessed at five 1-minute intervals. Each resin sealant was exposed using its manufacturer recommended LCU and also with LA. Data analysis was performed using software (GraphPad Prism 10.0.2) employing ANOVA at a pre-set alpha of 0.05. RESULTS: For each sealant, both SP-30s and MP-10s achieved a higher DC than LA-1s. While SP-30s surpassed LA-2s, MP-10s equaled LA-2. There was no DC difference between LA-3, SP-30s, and MP-10s. MP-3s was not different from LA2s. CONCLUSIONS: Using manufacturer's suggested LCU and exposure yielded higher DC than a 1-second laser exposure. Extending laser exposure to 3 seconds made DC values comparable. Further research is needed to address clinical ramifications of employing a laser-diode LCU. IMPLICATIONS: Using the manufacturer-recommended light-curing unit (LCU) and cure duration yielded results similar to those of the 3-second exposure with the LA curing light, but not to the 1-second cure suggested by the LA manufacturer. Employing a 3-second LA curing light method could be a suitable option for placing sealants (small areas) in uncooperative children and patients who would benefit from reduced chair time.